Mulheres escravas e forras na Ribeira do Acaraú (1750-1788) - Galdino, Maria Rakel Amancio (2013)
The investigation that resulted in this paper examined the insertion and presence of black slavery throughout the eighteenth century in the northwestern state of Ceará, where most of the territory was entitled Ribeira Acaraú. Therefore, stood out the performances of slave and free women and from the experiences of them, we have analyzed the changes in this society that enabled the rise and dominance of Africans and their descendants in the world of captives. Through consultation with various documentary sources as cartorárias, records of the Chamber of Sobral, correspondences between the settlers and the Overseas Council, parish records and the crossing of the information contained in these, one can observe different situations regarding this society, the world of work and the network construction workers solidarity possible slaves and freedmen in a region agropastoral and predominance of family labor. Entering the universe of captives through the experience of women, it is observed that the performance of these was permeated with intent to survive, preserve their families, and even achieve freedom. To reassure them, the women worked, sought union sanctified by the church, engaged in crony relationships, which enable them to have the protection and solidarity of a network formed by free persons freed (blinders), other slaves and even gentlemen. The sources consulted in line with the discussion, allowed the observation that at least in the case of captives and ceilings, usually inserted in small flocks, labor and solidarity were strategic elements to meet the challenges and limitations imposed by slavery.